The Czech version of the Utian Quality of Life Scale questionnaire assessing women’s quality of life during menopause - Moravcová, Markéta; Mareš, Jiří; Horáčková, Kateřina (My University, 2022)
Introduction Menopause is a physiological process, forming a part of a lifetime that most women go through. This period of life is briefly described by experts as a triple transformation: biological, social, and psychological. For menopausal women, health care professionals can use one of 10 specific questionnaires to assess health-related quality of life and its symptoms. The authors herein speak about the preparation of a Czech version of one such questionnaire – the Utian Quality of Life Scale (UQOL). Material and methods A Czech version of the UQOL was created by repeated and backward translation. It was validated on a sample of 204 women after natural menopause (45–65 years old). We judged the reliability of the Czech version of UQOL using Cronbach’s a. We assessed the instrument’s validity by means of confirmation factor analysis. Results The authors modified the original version of the UQOL. The Czech version has 4 new domains with 18 items. This form was created using the results of confirmation factor analysis. Conlusions The Utian Quality of Life Scale questionnaire is completed by the women themselves, thus meeting the golden rule of all quality-of-life research stating that the primary source should be data from the client him/herself. However, this requirement raises some methodological problems.
Česká verze dotazníku Utian Quality of Life Scale hodnotícího kvalitu života žen v souvislosti s menopauzou
Keywords: assessing; menopause; quality of life; Utian Quality of Life Scale; hodnocení; menopauza; kvalita života; Utian Quality of Life Scale